Dissolved Organic Matter in Wetlands - Alan L. Wright; K. Ramesh Reddy (EDIS, 2009)
SL-294, a 3-page illustrated fact sheet by Alan L. Wright and K. R. Reddy, describes the importance of dissolved organic matter and its role in regulating nutrients in terrestrial and aquatic ecosystems. Published by the UF Department of Soil and Water Science, June 2009.